Behavioural Biases and Investment Decisions of Individual Investors: Evidence from the Nepalese Stock Market - Basnet, Silendra Kumar; Sah, Kiran Kumari; Shah, Binod (Dristikon: A Multidisciplinary Journal, 2026)
The aim of the study is to analyze the impact of behavioral biases on the investment decision of individual investors in the Nepalese stock market. The research has followed descriptive and causal comparative research design. Primary data were collected using a convenience sampling technique through a structured questionnaire which was examined by the researcher. The questionnaire items represented four categories: overconfidence bias, disposition effect bias, anchoring bias, and herding bias. To assess the relationship between behavioral biases and investment decisions, the statistical correlation analysis and regression technique were used. The analysis performed on the data collected appears to give a fairly accurate view of the average equity investor in the NEPSE. Experienced and knowledgeable investors would readily admit that the structure and relative weights of the chosen categories reflect on the average, a still unsophisticated and immature investor profile. The study concluded that two, namely overconfidence and herding, have a strong influence on the investment decisions of individuals. The current research also emphasized that participants in financial markets are not rational in their decision-making process, and even their choices are limited. This study has provided evidence that investors have overconfident biases due to positive coefficient in the model tested. This overconfidence bias influences the decisions with respect to investor’s investments. Overconfident investors believe that they are better investors than both their peers and a stock market index.